Red-Shifting Blue Light Photoredox Catalysis for Organic Synthesis: A Graphical Review - Beck, Logan R.; Xie, Katherine A.; Goldschmid, Samantha L.; Kariofillis, Stavros K.; Joe, Candice L.; Sherwood, Trevor C.; Sezen-Edmonds, Melda; Rovis, Tomislav (SynOpen, 2023)
Photoredox catalysis has revolutionized synthetic chemistry in recent decades. However, the field has traditionally used high-energy blue/ultraviolet light to activate chromophores. High-energy irradiation is associated with several drawbacks (e.g., activation of sensitive functional groups, undesired metal-ligand homolysis, background activation of molecules, and poor penetration), which has led researchers to develop alternative systems with lower energy deep red (DR) or near-infrared (NIR) light. This graphical review provides a concise overview of photophysical principles relevant to photoredox catalysis. Several applications that benefit from low-energy irradiation, such as large-scale batch reactions, photodynamic therapy, biological labeling, and multi-photon excitation are reviewed.
Keywords: photoredox catalysis; deep red and near-infrared light; cross-coupling; reaction engineering; photodynamic therapy; photoaffinity labeling; proximity labeling; multiphoton excitation